2016
DOI: 10.1097/id.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High Insertion Torque Versus Low Insertion Torque on Marginal Bone Resorption and Implant Failure Rates

Abstract: The current review indicated that there is no significant difference in marginal bone resorption and implant failure rate between implants inserted with high or low insertion torque values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 22 publications
2
35
3
1
Order By: Relevance
“…In the present study, no correlation between IT and marginal bone loss after one year could be seen, which is in line with the conclusions of a recent meta-analysis of the literature including studies with reported ITs from < 25 to 176 Ncm [35]. Interestingly, our data showed that also low IT resulted in ISQ levels that are considered to indicate sufficient stability, even for early loading protocols [30, 36].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, no correlation between IT and marginal bone loss after one year could be seen, which is in line with the conclusions of a recent meta-analysis of the literature including studies with reported ITs from < 25 to 176 Ncm [35]. Interestingly, our data showed that also low IT resulted in ISQ levels that are considered to indicate sufficient stability, even for early loading protocols [30, 36].…”
Section: Discussionsupporting
confidence: 91%
“…Concerns have been expressed that too high IT may induce pressure necrosis and marginal bone resorption [35]. In the present study, no correlation between IT and marginal bone loss after one year could be seen, which is in line with the conclusions of a recent meta-analysis of the literature including studies with reported ITs from < 25 to 176 Ncm [35].…”
Section: Discussionsupporting
confidence: 90%
“…32 However, in many articles, insertion torque and implant survival have been reported to be irrelevant. 34 However, implant failure rates were significantly higher for a low insertion torque of <20 Ncm in this study over a long-term (10-year) follow-up. All of their implants were successful, and a histologic examination showed that the bone-implant contact was not related with the insertion torque.…”
Section: Discussioncontrasting
confidence: 56%
“…33 The systematic review of Berardini and colleagues also found no significant difference in implant failure between fixtures installed with high and low insertion torques. 34 However, implant failure rates were significantly higher for a low insertion torque of <20 Ncm in this study over a long-term (10-year) follow-up.…”
Section: Discussioncontrasting
confidence: 56%
“…Khayat These finding were confirmed by a recent meta-analysis which concluded that implant failure and marginal bone loss were not affected by high insertion torque. 43 On the contrary, high insertion torque is necessary for good primary stability, which is essential for prevention of micromotion and the establishment of osseointegration. 44 Primary stability is largely a property of the implant size, shape, and width, which is provided by a tapered design and increasing implant diameter.…”
Section: Discussionmentioning
confidence: 99%